Exploring the effects of climate change communication and training efforts: lessons from training-courses aimed at mid-career professionals - Van Wyk, Claire (African Climate and Development Initiative, 2017)
Research on the different ways in which climate change and adaptation (CCA) is communicated and taught has been growing in popularity over the last few decades. Researchers in communication science have found that the way in which information is presented and transferred is important in influencing people's perceptions and attitudes towards particular topics and issues. With this in mind, the lack of interest or realization of the severity of climate change at many levels of governance may be indicative that climate change, the subsequent negative impacts thereof and the need to implement adaptive and mitigative strategies - is not being effectively communicated to these audiences. This research explores the effect of CCA training-courses on participant knowledge, perceptions and attitudes towards CCA and related issues. It also highlights training methods and elements of course design which participants identified as enabling factors in enabling their understanding of CCA. The data collection used a mix methods approach, and focused around two training-courses. Participants (n=37) were mid-career professionals, many of whom engage in decision-making and policy development activities in different levels and sectors of government. Quantitative data was collected using scaled pre-and-post training tests. Qualitative data was collected through 14 semi-structured interviews, process observations, and anonymous feedback slips. A majority of participants (68%), showed an increase in knowledge scores after attending training. Similarly, 62% of participants responded more positively to questions relating to CCA in the post-training test compared to their pre-test responses. This research did not find a strong correlation between changes in knowledge, and changes in perceptions and attitudes; however, there were positive changes in all three variables. Participants discussed six methods of teaching and training which enabled their understanding of CCA and related issues; namely, PowerPointTM presentations, group work, practical exercises, games and role-play. Learnings from studying the training-courses highlight the importance of collaborative learning, diversity in participant groups, active engagement of participants with various mixed training methods and careful framing of content such that it inspires a sense of confidence rather than hopelessness. The effective communication and transfer of CCA information to professionals that are engaged in decision-making and policy development is key to increasing adaptive capacity, and subsequently adaptation at scale. It is therefore critical that CCA communication and capacity building efforts, such as training-courses, are designed such that they optimize participant learning and understanding.